Nietzsche’s Übermensch: the notion of a higher aristocracy of the future (2010)
The article discusses the idea of Übermensch in Nietzsche as part of his critique to Christianity and the crisis of modernity. The idea of Übermensch is expounded in most of his Works in particular in his books: Thus Spoke Zarathustra and The Gay Science. A new man that has overcome the tyranny of religion and modern reason: the higher aristocracy of the future. The article explores the relationship between Übermensch and religion; Übermensch and man; Übermensch and will to power. With the aim of outline some political implications of the idea of Übermensch with regard to political theory.